Amsal 29:14 dan “Salipuri Temmadinging”: Dialog Nilai Kebijaksanaan tentang Kepemimpinan - Huliandro Di’Almon Pan (Jurnal Magistra, 2026)
This article aims to explore a dialogical reflection on the values of wisdom and leadership between the Bugis local wisdom of Salipuri Temmadinging and the biblical wisdom tradition found in Proverbs 29:14. The study is motivated by the growing leadership crisis in contemporary society, which calls for ethical reflections rooted not only in modern theories but also in local and religious traditions rich in moral insight. Employing a qualitative approach with a literature-based method, this research conducts a critical and comparative analysis of cultural texts on Salipuri Temmadinging and biblical interpretations of Proverbs 29:14. The findings reveal that both traditions emphasize social justice, moral integrity, and advocacy for the poor as essential foundations of stable and legitimate leadership. Leadership is understood not as an instrument of power, but as a moral responsibility to protect, nurture, and sustain communal life. The dialogue between these traditions highlights justice as a structural principle that ensures the durability and credibility of leadership. This study implies that integrating local wisdom and biblical wisdom literature can contribute significantly to the development of ethical and contextual leadership models within Indonesia’s pluralistic society.